Frequency of Failed Spinal Anesthesia and Associated Factors in Cesarean Section at Mardan Medical Complex, Mardan, KP, Pakistan - Shabir Ahmad; Abdul Qadeer; Roohul Amin; Saeed Anwar; Hamid Ullah; Omama Akmal; Tahir Khan (International Journal of Women's Health Nursing And Practices, 2024)
Objective: Spinal anesthesia is the preferred choice of anesthesia for parturients having cesarean sections. Despite the high percentage of success in providing acceptable surgical anesthesia, failure of spinal anesthesia has been reported. This study aims to determine the frequency and associated factors related to failed spinal anesthesia during cesarean sections in pregnant women. Methodology: This descriptive cross-sectional study included 149 pregnant women and was conducted at Mardan Medical Complex (MMC) between April and September 2023. Pregnant women having cesarean sections elective or emergency were administered 10–15 mg of 0.75% hyperbaric bupivacaine using a 23–25G Quincke spinal needle. A pre-designed questionnaire was used to document patient demographics, clinical details, as well as spinal anesthesia details of each patient. All the variables were analyzed with the help of SPSS version 22. Results: Among the 149 pregnant women who received spinal anesthesia, 17 (11.4%) experienced “failed” outcomes, where the spinal anesthesia did not work as intended. Conversely, 132 (88.6%) had “successful” outcomes, indicating effective administration of spinal anesthesia. A portion of 11 (8.7%), represented “partial failure,” where the anesthesia had some success but did not achieve adequate anesthesia. While complete failure accounted for 4 (2.7%) of cases, signifying instances where spinal anesthesia did not work completely. Conclusion and Recommendations: The frequency of failed spinal anesthesia in pregnant women undergoing cesarean section at MMC was high at 11.40%.
Keywords: Cesarean section; associated factors; failed spinal anesthesia; spinal anesthesia